The rise of Africa’s processing sector and commercialization of smallholder agriculture - Badiane, Ousmane; Collins, Julia; Glatzel, Katrin; Tefera, Wondwosen (AKADEMIYA2063, 2022)
Across many parts of Africa, commendable progress has been made in recent years to increase agricultural productivity; reduce hunger, malnutrition, and poverty; create new employment opportunities; and improve the livelihoods of rural communities. Yet, demographic change, urbanization, shifting diets, and climate change mean that pressure is growing on food systems to make more varied and nutritious food available and accessible. Coupled with continued population growth, the significant economic growth experienced over the past two decades has accelerated food demand, leading to rapid increases in food imports despite strong agricultural sector growth (Christiaensen 2020; Seleshi 2021).